First records of four exotic slugs in Argentina - Gutierrez Gregoric, Diego Eduardo (2013)
This paper reports for the first time the occurrence of four exotic terrestrial slug species in Argentina: Lehmannia valentiana (Férussac, 1823) (Limacidae), Deroceras invadens Reise et al. 2011 (Agriolimacidae), Arion intermedius Normand, 1852 (Arionidae) and Meghimatium pictum (Stolyczka, 1873) (Philomycidae). The study is based on specimens deposited in museums in Argentina. Both the morphologic characteristics and the mitochondrial cytochrome oxidase I gene sequences were used to identify the exotic species. Phylogenetic analyses were also carried out in order to explore the location of their origins. Lehmannia valentiana had the oldest records and has been widely distributed in Argentina. Deroceras invadens and A. intermedius were found to be restricted to the southern portion of the country. Meghimatium pictum was recorded in the northwest and northeast Argentina, and the DNA sequences analyzed from this species were more closely related to specimens from the west of the Strait of Taiwan. A determination of the origin of the other species was impossible because either the sequences analyzed grouped with samples from different geographical origins or only few sequences were available for comparison. In view of the invasive potential of these slug species, the present work provides new and potentially useful DNA sequence data obtained from morphologically-confirmed specimens. Information provided from these analyses should assist in making a rapid identification of these exotic slugs by nonspecialists and governmental authorities who are responsible for managing and controlling the presence of exotic species.